Megalota festuca Pinkaew and Muadsub (Lepidoptera: Tortricidae: Olethreutinae), a new species from Thailand - Pinkaew, Nantasak; Muadsub, Sopita (Zootaxa, 2021)
Megalota festuca sp. nov. is described as new to science. Illustrations of adults and genitalia are provided. This new taxon increases the number of described Megalota species to 48 worldwide and to 3 in Thailand. A key to Megalota species in Thailand is also provided.